If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t + 13 = 3 Reorder the terms: 13 + t = 3 Solving 13 + t = 3 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + t = 3 + -13 Combine like terms: 13 + -13 = 0 0 + t = 3 + -13 t = 3 + -13 Combine like terms: 3 + -13 = -10 t = -10 Simplifying t = -10
| 8t^2+17t-25=0 | | X=18-11 | | f(x)=4x^2+8x+11 | | 7.09=3+y | | -6n+48=6u | | 1+12= | | -7x-2(11+2y)=-13 | | 0.2x-1.8=-4.2 | | 672-3x=448-2x | | x-4*3=5 | | m=3-7 | | 10x+110=12x+96 | | 11*3x=20 | | 11*3x=17 | | 11*3x=2 | | 708=n+300 | | 9(x+8)=5[x-(8-x)] | | 1.2y-12=-2.8y-25.2 | | x=24+15 | | n-305=225 | | -3x+5x-4x=13 | | 6h-11-h=4-37h-2 | | 6h-11-h=4-37h-3 | | 5x-8=4x+3(x+1) | | 4-3x=274 | | A/36=3/8 | | 5.6+x=6.3 | | 5d+10+4=13.50 | | 0.6x-1.2=8.4 | | 0=12x^2+8-15 | | 5.6+x= | | Log(9)(x+2)=log(9)(3x+5) |